(-)-Kolavenic acid - Zukerman-Schpector, Julio; Madureira, Lucas Sousa; Messiano, Gisele B. [UNESP]; Lopes, Lucia Maria Xavier [UNESP]; Tiekink, Edward R. T. (Blackwell Publishing, 2008)
In the two, almost identical, molecules in the asymmetric unit of the title compound [ systematic name: (E)-3-methyl-5-(1,2,4a, 5-tetramethyl-1,2,3,4,4a,7,8,8a-octahydronaphthalen-1yl) pent-2-enoic acid], C20H32O2, the rings are trans fused. The cyclohexane ring has a chair conformation and the cyclohexene ring a distorted half-boat conformation. The two independent molecules are connected into a dimer via O-H center dot center dot center dot O hydrogen bonds. The dimers are associated into supramolecular chains along c via C-H center dot center dot center dot O contacts.